2023
DOI: 10.13057/biodiv/d240862
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Blumea balsamifera leaf extracts from Aceh, Indonesia

MASYUDI MASYUDI,
ANITA NOVIYANTI,
MUHAMMAD RIDHWAN
et al.

Abstract: Abstract. Masyudi, Noviyanti A, Ridhwan M, Nurman S, Jailani, Armi, Rafsanjani TM, Usman S, Hanafiah M, Marlina. 2023. Antibacterial activity of Blumea balsamifera leaf extracts from Aceh, Indonesia. Biodiversitas 24: 4584-4589. Blumea balsamifera L. has long been used as traditional medicine by communities in Aceh, Indonesia and from various parts of the world. For generations, this plant has been believed to have properties to cure various diseases. The results of the GCMS analysis of B. balsamifera leaf fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…2017) observed that ethyl acetate was the most active fraction in inhibiting the bacteria compared to the n-hexane and methanol fractions. Masyudi et al (2023) also reported that ethyl acetate extract of Blumea balsamifera leaves showed the largest inhibitory zone diameter compared to ethanol and hexane extract of Blumea balsamifera leaves could inhibit the growth of Staphylococcus aureus and Pseudomonas aeruginosa. The ethyl acetate fraction attracts semi polar compounds in S. quadrifida leaves extract, which can inhibit bacterial growth.…”
Section: In Vitro Antibacterial Testmentioning
confidence: 92%
“…2017) observed that ethyl acetate was the most active fraction in inhibiting the bacteria compared to the n-hexane and methanol fractions. Masyudi et al (2023) also reported that ethyl acetate extract of Blumea balsamifera leaves showed the largest inhibitory zone diameter compared to ethanol and hexane extract of Blumea balsamifera leaves could inhibit the growth of Staphylococcus aureus and Pseudomonas aeruginosa. The ethyl acetate fraction attracts semi polar compounds in S. quadrifida leaves extract, which can inhibit bacterial growth.…”
Section: In Vitro Antibacterial Testmentioning
confidence: 92%